Body Mass Index and Height in the Friedreich Ataxia Clinical Outcome Measures Study. (12th December 2021) - Patel, Maya; McCormick, Ashley; Tamaroff, Jaclyn; Dunn, Julia; Mitchell, Jonathan A.; Lin, Kimberly Y.; Farmer, Jennifer; Rummey, Christian; Perlman, Susan L.; Delatycki, Martin B.; Wilmot, George R.; Mathews, Katherine D.; et al.
Abstract : Background and Objectives: Body mass index (BMI) and height are important indices of health. We tested the association between these outcomes and clinical characteristics in Friedreich ataxia (FRDA), a progressive neuromuscular disorder. Methods: Participants (N = 961) were enrolled in a prospective natural history study (Friedreich Ataxia Clinical Outcome Measure Study). Age- and sex-specific BMI and height Z-scores were calculated using CDC 2000 references for participants younger than 18 years. For adults aged 18 years or older, height Z-scores were also calculated, and absolute BMI was reported. Univariate and multivariate linear regression analyses tested the associations between exposures, covariates, and BMI or height measured at the baseline visit. In children, the superimposition by translation and rotation analysis method was used to compare linear growth trajectories between FRDA and a healthy reference cohort, the Bone Mineral Density in Childhood Study (n = 1, 535 used for analysis). Results: Median age at the baseline was 20 years (IQR, 13–33 years); 49% (n = 475) were women. A substantial proportion of children (17%) were underweight (BMI-Z < fifth percentile), and female sex was associated with lower BMI-Z (β = −0.34, p < 0.05). In adults, older age was associated with higher BMI (β = 0.09, p < 0.05). Regarding height, in children, older age (β −0.06, p < 0.05) and worse modified Friedreich Ataxia Rating Scale (mFARS) scores (β = −1.05 for fourth quartile vs first quartile, p < 0.01) were associated with shorter stature. In girls, the magnitude of the pubertal growth spurt was less, and in boys, the pubertal growth spurt occurred later ( p < 0.001 for both) than in a healthy reference cohort. In adults, in unadjusted analyses, both earlier age of FRDA symptom onset (=0.09, p < 0.05) and longer guanine-adenine-adenine repeat length (shorter of the 2 GAA repeats, β = −0.12, p < 0.01) were associated with shorter stature. Both adults and children with higher mFARS scores and/or who were nonambulatory were less likely to have height and weight measurements recorded at clinical visits. Discussion: FRDA affects both weight gain and linear growth. These insights will inform assessments of affected individuals in both research and clinical settings.